2015
DOI: 10.1016/j.ultsonch.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic cavitation erosion of nodular cast iron with ferrite–pearlite microstructure

Abstract: The cavitation erosion of ductile cast iron with ferrite-pearlite microstructure was analyzed based on ultrasonic experiments performed according to ASTM G32-2010 and the resistance was compared to the C45 steel with similar hardness. The microstructural observation of the surface for different exposure times to the ultrasonic cavitation reveals the fact that the process initiates at the nodular graphite-ferrite interface and is controlled by micro-galvanic activities and mechanical factors. The cavitation ero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The significantly increased solidification rate of the printed alloy created a more homogenous structure, with considerably reduced amounts of secondary pearlite phase. In contrast, the lower solidification rate of the reference alloy created a relatively large amount of pearlite phase that could consequently generate a micro-galvanic corrosion attack of the α-Fe matrix [23,24]. This micro-galvanic effect can explain the existence of a large number of corrosion sites on the external surface after exposing the alloy to a corrosive environment.…”
Section: Discussionmentioning
confidence: 99%
“…The significantly increased solidification rate of the printed alloy created a more homogenous structure, with considerably reduced amounts of secondary pearlite phase. In contrast, the lower solidification rate of the reference alloy created a relatively large amount of pearlite phase that could consequently generate a micro-galvanic corrosion attack of the α-Fe matrix [23,24]. This micro-galvanic effect can explain the existence of a large number of corrosion sites on the external surface after exposing the alloy to a corrosive environment.…”
Section: Discussionmentioning
confidence: 99%
“…The values for the mean depth of erosion (MDE) and mean depth of erosion rate (MDER) were determined based on the mass loss determined by periodically weighting the samples [19]. Figure 8 and Figure 9 show the MDE and MDER vs. the exposure time for two powers used in the laser re-melting phase (2400 and 2600 W) and reflect the corresponding cavitation erosion behavior.…”
Section: Resultsmentioning
confidence: 99%
“…In the Cavitation Laboratory of Timisoara Polytechnic University, the characteristic curves representing the cavitation erosion process taking place in the vibrating standard device with piezoelectric crystals are constructed with the relations presented by Bordeasu and his collaborators [1,5], which for the erosion velocity has the following form: (1) Even if till now, this relation proved satisfaction for the required exigency necessar y to cavitation erosion resistance analyze, it has been found that for materials having a very close behavior to cavitation erosion it is relatively difficult to establish which is the better one. For such purposes were applied supplementary microscopic analyzes regarding the eroded structure.…”
Section: Proposed Model Mathematical Form Of the Mean Depth Erosion Rmentioning
confidence: 99%
“…time t 3 and the corresponding erosion rate v 3 = v max = MDER max (4) 3-also from the experimental data it is chosen the stable value of the erosion rate v s = MDER s , at the final period of the cavitation exposure (165 min for the tests realized in our laboratory). We propose for this value the mean of the last four measured points: (5) With this data there can be determined also the values for the constants A and C which depend strictly by those values:…”
Section: Checking the Confidence Degreementioning
confidence: 99%